Pendidikan Segregasi, Integrasi Dan Inklusi - Akhmad Akbar; Tiara Utami; Pauziah Pauziah; Opi Andriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Segregated education is an educational service that separates educational services between children with special needs and normal children, schools for children with special and normal needs. In the form of special schools and special primary schools. Integrated education is an integrated education service that unites children with special needs and normal children in the same class and at the same school as normal children. Integration education services are divided into regular classes, regular classes with special guidance rooms and special classes. And inclusive education services are educational services that are carried out in a sustainable, planned and directed manner to develop the potential that exists in children with special needs so that they can adapt to their environment. Inclusive education services have several educational service models such as the regular class model, cluster model, Pull Out model, cluster and Pull Out model, special class model and full special class model.